Implementation Of The Islamic Boarding School-Based Program At SMP Azzainiyyah - Iis Farida Zein; Hanafiah; Ryan Yustian; Acep Dani Ramdani; Ipan Sopandi (Risalah, Jurnal Pendidikan dan Studi Islam, 2023)
The Ministry of Education and Culture (Kemendikbud) and the Ministry of Religion (Kemenag) are collaborating to implement the Islamic Boarding School-Based School Program. This collaboration is outlined in a joint agreement between the Director of Junior High School and the Director of Diniyah Education and Islamic Boarding Schools Number 815/C3/LL/2008 and Number Dt.I.III/83/2008 concerning the Development of Islamic Boarding School-Based Junior High Schools and continued based on the Agreement between the Director of Junior High School Development and the Director of Diniyah Education and Islamic Boarding Schools Number 1763.1/C3/KP/2013 and Number Dj.I/Dt.i.III/3/PP.00.7/2509/2913 concerning the Development of an Islamic Boarding School-Based Junior High School. Azzainiyyah Junior High School is one of the Islamic boarding school-based junior high schools that integrates the culture of Islamic boarding school in school by adding Islamic boarding school subjects sourced from the Traditional Islamic book completed by the scoring system of the report. This program has become one of the leading programs in the education world which answers the concerns of experts about non-religious scientists or scholars who only care about religion, with this program it is hoped that scientists who are religious and accomplished will be born. This research was carried out with a qualitative approach to reveal and interpret various symptoms and phenomena as well as analytical descriptive methods to always maintain the integrity of the subject, the data collected was analyzed more comprehensively.